Counterterrorism and Human Rights: A Global Perspective - Rashidiani, Farnoosh (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
This paper explores the intricate balance between counterterrorism measures and the protection of human rights, with a focus on liberal democracies. It examines how practices such as detention without trial, torture, and extrajudicial killings infringe upon fundamental human rights, which are essential for human dignity. Through case studies, including Northern Ireland in the 1970s and the United States’ post-9/11 “war on terror,” this paper highlights the key mechanisms shaping counterterrorism strategies and their broader implications for civil liberties. The research engages with international law and human rights frameworks, analyzing the impact of counterterrorism efforts on the global protection of human rights. Furthermore, the paper addresses a critical gap in the academic literature: the limited discussion surrounding the effectiveness of counterterrorism policies in achieving security while maintaining rights standards. A comparative analysis of international and national court decisions, including the European Court of Human Rights and the UK Supreme Court, is conducted to illustrate judicial reasoning in counterterrorism cases, particularly concerning the proportionality test. This study concludes that existing counterterrorism policies often fail to justify the extensive curtailment of rights, particularly where their effectiveness remains uncertain. The paper calls for more rigorous, empirical evaluation of counterterrorism measures, advocating for the development of standardized models that assess both security outcomes and broader societal impacts. By doing so, it aims to contribute to a more nuanced discourse on counterterrorism and human rights at a global level.